Status in Management and Organizations - Pearce, Jone L. (Cambridge : Cambridge University Press, 2010)
People go to extraordinary lengths to gain and defend their status. Those with higher status are listened to more, receive more deference from others, and are perceived as having more power. People with higher status also tend to have better health and longevity. In short, status matters. Despite the importance of status, particularly in the workplace, it has received comparatively little attention from management scholars. It is only relatively recently that they have turned their attention to the powerful role that social status plays in organizations. This book brings together this important work, showing why we should distinguish status from power, hierarchy and work quality. It also shows how a better understanding of status can be used to address problems in a number of different areas, including strategic acquisitions, the development of innovations, new venture funding, executive compensation, discrimination, and team diversity effects.
Title from publisher's bibliographic system (viewed on 09 Oct 2015).
Keywords: Organizational sociology; Organizational behavior; Industrial sociology; Social status; Prestige